2019
DOI: 10.1021/acs.orglett.9b04193
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of the Organocatalyzed Aerobic Oxidation of Aldehydes to Acids

Abstract: The organocatalyzed aerobic oxidation of aldehydes to acids was reproduced from the original report. In- and ex-situ analysis of the reaction mixture as the function of time reveals that, unlike the claim in the publication, the aerobic oxidation of aromatic and aliphatic aldehydes leads predominantly to the formation of peracids. The latter are transformed into the corresponding carboxylic acids during the workup procedure. The buildup of peracids in solution poses safety problems that should not be overlooke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 51 publications
(40 reference statements)
3
48
1
Order By: Relevance
“…We have recently shown that 17 is easily transformed into the corresponding carboxylic acid 2a. 25 There has been speculation on the mechanism of formation products with one carbon less than expected but the only hypothesis (i.e. isomerization) was ruled out.…”
Section: Reactivity Of Aldehydes 7 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that 17 is easily transformed into the corresponding carboxylic acid 2a. 25 There has been speculation on the mechanism of formation products with one carbon less than expected but the only hypothesis (i.e. isomerization) was ruled out.…”
Section: Reactivity Of Aldehydes 7 Andmentioning
confidence: 99%
“…Proposed aerobic oxidation pathway of products with one carbon less than expected (i.e. compounds 13 from aldehyde 7) (adapted from25,[27][28] A mixture of aldehydes 7 and 8 (60/40) was synthesized according to the work of Lemaire et al29 and was oxidized under similar experimental conditions. At 150°C, the total conversion of a mixture of aldehydes 7 and 829 was obtained in less than 30 min(Figure 7).…”
mentioning
confidence: 99%
“…As concerns the mechanism of the NHPI‐catalyzed aldehyde oxidation, it was originally hypothesized that as a result of a free radical chain reaction, a peracid ( I ) is formed as an intermediary product that would readily furnish the corresponding carboxylic acid with the involvement of a remaining aldehyde via a Criegee intermediate ( II ) [7b,11] . It was later highlighted that the formation of the Criegee intermediate from aldehydes is very slow, thereby resulting in considerable accumulation of peracid in the crude reaction mixture [7a,12] . In this manner, the formation of the carboxylic acid product ( III ) should rather be explained by the decomposition of the peracid, for example, during aqueous work‐up [12] .…”
Section: Introductionmentioning
confidence: 99%
“…It was later highlighted that the formation of the Criegee intermediate from aldehydes is very slow, thereby resulting in considerable accumulation of peracid in the crude reaction mixture [7a,12] . In this manner, the formation of the carboxylic acid product ( III ) should rather be explained by the decomposition of the peracid, for example, during aqueous work‐up [12] . It was recently demonstrated that carboxylic acid III may also be formed via dimerization of acylperoxy radical IV [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Following unsuccessful trials on catalyst-free and platinum-catalyzed aerobic aldehyde oxidations (see the Supporting Information for details), 17 a novel flow method was attempted by using N -hydroxyphthalimide (NHPI) as a homogeneous oxidation catalyst in the presence of molecular O 2 as the oxidant. 18 The reaction was investigated in nitromethane so that it would be compatible with the organocatalytic conjugate addition upon telescoping. Following parameter optimization ( Tables S8 and S9 ), quantitative and selective oxidation of 2 was achieved by using the setup depicted in Figure 2 .…”
mentioning
confidence: 99%